Diversity and Species Composition of Midgut Symbiotic Bacteria in Culex quinquefasciatus Mosquitoes in Gampaha District, Sri Lanka - Randi Hathnagoda; Pinidi Gunathilake; Thilini Buddhinee; Pabasara Welgama; Hasini Gunarathna; Harshani Perera; Koshila Ranasinghe (Journal of Tropical Medicine)
Mosquitoes, notorious for their deadly impact as disease vectors, also hold economic value owing to their roles in disease transmission. The present study focuses on the importance of understanding mosquito gut microbiota for implementing innovative vector control strategies, thereby mitigating disease transmission. The study was conducted in the Gampaha Medical Office of Health (MOH) area of Sri Lanka with the focus of elucidating the microbial diversity within the midgut of Culex quinquefasciatus, a crucial step to support ongoing paratransgenesis efforts. Sampling was performed by utilizing standard mosquito sampling techniques and their midgut homogenates were plated on Plate Count Agar to isolate bacteria, which were then identified through biochemical tests. Subsequently, the most abundant bacterial families were subjected to DNA extraction, PCR amplification, and gene sequencing for species identification. The study revealed the presence of four bacterial families (Staphylococcaceae, Streptococcaceae, Neisseriaceae, and Moraxellaceae) in adult mosquitoes, while larvae harbored an additional family, Micrococcaceae. Interestingly, the relative distribution of midgut bacteria varied significantly among field-caught larval and adult strains from different study areas (chi-square = 1.673; P<0.05), indicating similar bacterial flora across mosquito life stages and geographical locations. Of particular interest is the identification of Lysinibacillus sphaericus, a bacterium with potential for paratransgenesis applications. Given the high mosquito density in the study area, leveraging paratransgenesis for Cx. quinquefasciatus control is recommended. Furthermore, insights into gut microbes could inform the integration of gut microflora from modified strains into existing Sterile Insect Technique (SIT) and Incompatible Insect Technique (IIT) approaches in Sri Lanka.